Inter-varietal sterility and fertility restoration in Oryza sativa Linn. - Abraham, OG; Faluyi, JO; Nwokeocha, CC (ORYZA-An International Journal of Rice, 2021)
This study explored the underlining reproductive factors that cause sterility in rice, using hybrids obtained from crosses among landrace selections and improved varieties. The study was carried out between 2016 and 2018. Nine landrace cultivars and two improved varieties were involved in the hybridization experiment. Among the 17 putative hybrids that were obtained, only 5 were confirmed as true hybrids. Meiotic chromosome studies and pollen studies in the F1, and Mendelian segregation studies for fertility in the F2 were carried out. Some F2 lines were monitored to F3 to ascertain the level of fixation of gene combinations for fertility. The results obtained from the chromosomal studies showed that phenomena such as laggards, precocious movements, formation of multivalents, and unequal segregation to the poles are associated with pollen sterility in all - 5 hybrids, at the F1 and F2 generations. The indehiscence of anthers contributed to infertility due to pollen shortage than the fertility of the pollens themselves. Even though in males, there is a preponderance of male sterility, female sterility is also a phenomenon that is possibly contributing to inter-varietal sterility. The segregational pattern of 13:3 was observed for fertility in the F2 which suggests the inhibition of fertility by a gene in the dominant state. There was the restoration of fertility in many of the lines advanced to the F3 to up to 93 % fertility. It was, therefore, concluded from the study that landraces of rice still hold the key for the rice crop improvement and should therefore be conserved.